can someone please help me with this question with explanation . I request no spammers
Attachments:
![](https://hi-static.z-dn.net/files/d8c/0948d6bb05374ccede6df59c11816a66.jpg)
Answers
Answered by
16
cos^4 (20) = cos^2(20)× cos^2(20) = cos^2(20) [ 1- sin^2 (20)]
=> similarly, sin^4 (20) = sin^2 (20) × sin^2(20)
sin^4 (20) => sin^2(20) [ 1 - cos^2(20)]
Now, coming to the given equation,
=> sin^2(20) + cos^4(20) / sin^4(20) + cos ^2(20)
=> {sin^2(20) + cos^2(20) [ 1- sin^2 (20)] } ÷ { sin^2(20) [ 1 - cos^2(20)] + cos^2 (20) }
Attachments:
![](https://hi-static.z-dn.net/files/db4/ae5bbc1b54b47475862f64eb7b8adf3f.jpg)
Answered by
3
Attachments:
![](https://hi-static.z-dn.net/files/d9f/d509294ebf9f3ff6bdfedf2804a637bb.jpg)
Similar questions